2022
DOI: 10.3390/app12104815
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Continuous-Wave Ti:Sapphire Laser with High-Intensity Pumping Using a Commercially Available Crystal

Abstract: Despite the importance of improving the efficiency of lasers in order to expand their utility range, the improvement of the efficiency of Ti:sapphire lasers has not progressed due to their high crystal losses. Therefore, we improved the efficiency of CW Ti:sapphire lasers by high-intensity pumping, which is one of the most effective methods of suppressing the efficiency reduction due to losses. Using a easily commercially available 0.25 wt.%, figure of merit (FOM) 200 Ti:sapphire crystal, optics and a pump sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although this result demonstrated good slope efficiency, approaching that expected from a 532 nm pump [14], most applications of Ti:sapphire demand near-diffraction limited output which we demonstrate in the next section by inserting an intracavity slit.…”
Section: Non-tem00 Outputmentioning
confidence: 79%
“…Although this result demonstrated good slope efficiency, approaching that expected from a 532 nm pump [14], most applications of Ti:sapphire demand near-diffraction limited output which we demonstrate in the next section by inserting an intracavity slit.…”
Section: Non-tem00 Outputmentioning
confidence: 79%
“…Although this result demonstrated good slope efficiency, approaching that expected from a 532 nm pump [14], most applications of Ti:sapphire demand near-diffraction limited output which we implement in the next section by inserting an intracavity slit.…”
Section: Non-tem00 Outputmentioning
confidence: 93%
“…In the theoretical analysis, we used quasi-three-level (quasi-four-level) laser rate equations with CW pumping, which include the spatial distribution of the pump and laser beams [17,[38][39][40][41]. In the case of quasi-three-level (quasi-four-level) lasers, as in the case of four-level lasers, for simplicity, we define the normalized incident pump power F, which is dimensionless with respect to the incident pump power on the gain medium P p , as…”
Section: Methodsmentioning
confidence: 99%
“…For hemispherical short-cavity CW Yb:YAG lasers, optical conversion efficiencies exceeding 75% for the incident pump power have also been achieved [15]. In addition, optical-to-optical conversion efficiencies exceeding 31% for the incident pump power have been achieved for T:sapphire lasers despite the use of commercially available high-loss Ti:sapphire crystals [16,17]. Using a theory that quantitatively reproduces the experimental results of Ti:sapphire lasers, it has been shown that even under conditions of a high intrinsic residual loss of 4%, an optical-to-optical conversion efficiency of 55.9%, approaching the quantum limit of Ti:sapphire lasers, can be achieved by using high-gain by high-intensity pumping [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation